Evaluation of the effective air-LNAPL saturation in lateritic soils with multimodal pore-size distribution - Soto, Miguel Alfaro [UNESP] (2019)
This paper aims to evaluate the suitability of the model developed by API (2007) in the indirect obtention of effective saturation curves for air-LNAPL systems in soils with lateritic characteristics and multimodal pore-size distribution, such as those found in different Brazilian territories. For this purpose, soil samples typical of the state of São Paulo were tested in order to determine the effective saturations of air-water and air-LNAPL systems from the hanging column test, as well as, filter paper method. The results showed typical retention curves of soils with multimodal pore size distribution, whether for air-water or air-LNAPL systems. Furthermore, obtaining effective air-LNAPL saturation curves from air-water systems were consistent, whenever trimodal capillary pressure models were used. Finally, as pointed out by Alfaro Soto and Chang (2015), it should be emphasized that the modification of prediction models of specific volumes of contaminants for remediation in tropical soils could be necessary due to their differentiated retention characteristics.